Magical Board Theatre: interactive stories that can be played on multiple boards: two educational prototypes - Lacet, Demetrius (2022)
Interactive storytelling uses in education are limited by the time required for its production and the ephemeral nature of interaction systems, leading inter-active stories to have a short usefulness life. We have developed the concept of platform-independent interactive stories, called virtual choreographies, enabling interactive stories to be replayed on novel technological platforms as they emerge, tackling the second half of this problem. The first part was also approached via a graphical storyboarding approach. Both aspects have been prototyped in a demonstration, called Magical Board Theatre (“Teatro de Tabuleiro Mágico”, original Portuguese name). We present this prototype, including its storyboarding tool, summarize the virtual choreographies ap-proach, and demonstrate how the prototype operationalizes them with story and platform examples.